Dynamics of non-Hermitian Floquet Wannier–Stark system - H P Zhang; K L Zhang; Z Song (New Journal of Physics, 2024)
We study the dynamics of the non-Hermitian Floquet Wannier–Stark system in the framework of the tight-binding approximation, where the hopping strength is a periodic function of time with Floquet frequency $\mathcal{ω }$ . It is shown that the energy level of the instantaneous Hamiltonian is still equally spaced and independent of time t and the Hermiticity of the hopping term. In the case of off resonance, the dynamics are still periodic, while the occupied energy levels spread out at the resonance, exhibiting t ^z behavior. Analytical analysis and numerical simulation show that the level-spreading dynamics for real and complex hopping strengths exhibit distinct behaviors and are well described by the dynamical exponents z = 1 and $z = 1/2$ , respectively.